Mechanical and Chemical Properties of Nano-SiO2 Geopolymer Cement Cured under Elevated Conditions towards Acid Invasions - YERIKANIA, UTAMI (2017)
In completing drilling operation, cementing job is conducted to restrict fluid movement between the formations and to bond and support the casing. Several factors may affect the mechanical properties of oilwell cement, including elevated condition and acid stimulation. Besides having mechanical properties degradation under elevated conditions, history shows that acid stimulation job may also cause zonal isolation problems toward conventional Portland-based oilwell cement. Geopolymer cement, a new developed-cement system, has been proven having excellent compressive strength and good acid resistance. However, its performances degraded under elevated conditions, especially due to acid attack. This research focuses on the compatibility of nano-SiO2 geopolymer cement cured under elevated conditions towards acid invasion. Class G cement, fly ash, silica fume and nano-SiO2 were used as raw materials in five (5) samples. It utilized two curing conditions (70oC/1500 psi and 120oC/4000 psi) for 24 hours and 12%/3% HCl/HF for acid solution. Cement samples were immersed into acid solution for 1, 3 and 5 days. The morphology of cement samples was identified using Scanning Electron Microscopy (SEM) whilst the chemical bond and composition were defined from Fourier Transform Infrared Spectrometer (FTIR) and X-Ray Fluorescence (XRF). Compressive strength and mass loss of the cement samples were then tested to be related to the structure of cement. This study found that NG1 (nano-geopolymer cement with 1% nano-SiO2) reached the highest strength value at elevated conditions. Compared to Class G, pure geopolymer (GPC) and nano-SiO2 geopolymer (NG1 and NG3) had better acid resistance as the experienced much less strength loss. At the same time the CO2 emissions from producing conventional API cement can be eliminated by the new nano-SiO2 geopolymer cement.